“They shouted at me to discontinue exclusive breastfeeding”: narratives of mothers in Limpopo Province of South Africa as they grabble with exclusive breastfeeding - Maponya, Nyabana Martha; Matlala, Sogo France (Bangladesh Journal of Medical Science, 2022)
Objective: Exclusive breastfeeding for the first six months of an infant’s life is an internationally recognised practice that promotes maternal and child health. Mothers and their infants reap health and socioeconomic benefits from exclusive breastfeeding. Even with these benefits, exclusive breastfeeding is still a challenge for some mothers to practice. Many studies revealed numerous challenges and enablers, and proposed comprehensive solutions, but implementation of exclusive breastfeeding for six months remains a challenge although there is some improvement. This study therefore explored barriers and facilitators to practice exclusive breastfeeding for the first six months of the infant’s life among mothers attending a health centre in Limpopo Province of South Africa, to contribute to the ongoing measures to increase the practice. Materials and methods: Mothers were selected through purposive sampling and semi-structured interviews were held with those willing to participate until saturation of data was reached. Interviews were audio-recorded, transcribed verbatim and analysed using a thematic analysis approach. Ethical issues of consent, permission and confidentiality were respected as well as trustworthiness criteria. Results and Discussion: Nine mothers narrated their experiences as they navigated through the exclusive breastfeeding practice. Education on exclusive breastfeeding and social support to a breastfeeding mother emerged as both barriers and facilitators to practice exclusive breastfeeding for six months. Conclusion: The study recommends that vigorous education on exclusive breastfeeding for six months be given to mothers during antenatal care and be extended to include relatives to empower them to support a breastfeeding mother. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 813-819